Near-infrared-light-induced decomposition of Rhodamine B triggered by localized surface plasmon at gold square dimers with well-defined separation distance - Satoshi Kaneko; Shuhei Watanabe; Shinya Kasai; Tomoaki Nishino; Kazuhito Tsukagoshi; Manabu Kiguchi (AIP Advances, 2019)
Localized surface plasmon-induced photoreactions at metal nanostructures have become central research topics in biology, catalysis, and analytical chemistry. In particular, the decomposition of organic pollutants is a popular topic. Rhodamine B is useful in the dye industry and biology; however, it is harmful to humans and the environment. In this study, we investigated the decomposition of the Rhodamine B molecule with a structurally well-defined array of gold square dimers. The array of gold square dimers was fabricated by electron beam lithography, which provided a homogenous well-defined reaction field. Continuous Raman spectral measurements using a near-infrared laser clearly showed that while the Rhodamine B molecules were stable in the absence of the gold square dimers, they were decomposed under near-infrared-light irradiation.